Demolition Mission Comic, Puzzles and Super Story ([Uk] Ladybird, 2015)
Over 500 logic puzzles, mind-benders and mathematical teasers compiled into twenty levels of ascending difficulty
Arts (Games)
13
Keywords: Arts (Games); Puzzles